The new managerial economics - Boyes, William J
Boyes introduces non-majors to the power of economics in business decision making. The text's intuitive approach clearly highlights how economics influences marketing, management, and other business-related decisions. In addition to traditional principles of price theory, Managerial Economics examines organizational behavior, strategic management, human resource management, and emerging issues such as game theory, TQM, and information economics